Education, Economic Growth and Personal Income Inequality across (Rich) Countries - Günther Rehme (Luxembourg Income Study (LIS), 2002)
This paper offers a supply-side explanation of the variation in long-run growth and inequality across countries. In the model education simultaneously affects growth and income inequality. More human capital may increase or decrease growth but also measured inequality. In contrast to some recent contributions the paper uses consistently defined data showing that higher (within-country) inequality is associated with lower growth in rich countries, even when controlling for initial income, education or fertility. Furthermore, (rich) countries that have a more productive education sector appear to have lower inequality. It is argued that institutions and policies which generate more high-skilled people or enhance the productivity of the education sector may affect long-run income equality and growth in a positive way.
Keywords: 330; Wirtschaftswachstum; Einkommensverteilung; Bildungsinvestition; Humankapital; Hochqualifizierte Arbeitskräfte; OECD-Staaten